Frequent Abdominal Pain in Childhood and Youth: A Systematic Review of Psychophysiological Characteristics. (13th March 2014) - Gulewitsch, Marco Daniel; Müller, Judith; Enck, Paul; Weimer, Katja; Schwille-Kiuntke, Juliane; Schlarb, Angelika Anita
Abstract : Background . Frequent abdominal pain (AP) in children and adolescents is often designated as functional gastrointestinal disorder. In contrast to research on psychological and social influences on the experience of AP in this population, psychophysiological features such as function of the autonomic nervous system, the central nervous system, or the endocrine system have rarely been studied. Methods . We conducted a systematic literature search for peer-reviewed journal articles referring to children with AP between 4 and 18 years. Studies on experimental baseline characteristics or reactivity of psychophysiological outcome parameters (autonomous nervous system, central nervous system, and endocrine parameters) were included. Key Results . Twelve of 18 included studies found psychophysiological differences between children with AP and healthy ones. These studies indicate a possible autonomic dysregulation and hypersensitivity of the central nervous system in children with AP following stimulation with stress or other intense stimuli. Mainly conflicting results were found regarding baseline comparisons of autonomic and endocrine parameters. Conclusions and Inferences . Frequent AP in children may be associated with an altered psychophysiological reaction on intense stimuli. It has to be considered that the current literature on psychophysiological characteristics of childhood AP is small and heterogeneous. In particular, multiparameter studies using validated experimental paradigms are lacking.